Feeding growing race horses in work - Ellis, Anrea D; Saastamoinen, M.T (MTT, 2008)
The athletic demands we put on horses in the racing industry require 1.5 to 3 year old, still growing horses, to be worked well above light exercise level. Therefore, the nutrient needs for such horses consist not only of maintenance, voluntary activity (play, group interaction) and growth but also of requirements for work. This leads to increased requirements for all nutrients. In practice, horse trainers alter energy intake of working youngsters according to body condition. The feeding levels are determined from experience and daily observation of horses and the choice of feed also often is made according to tradition and previous experience. Additional energy for growth and work is recommended for heat production when horses are kept in loose housing below thermal neutral temperature (Nordic countries). Although quality of protein is important, excess protein may have a detrimental effect on the performance of young horses. Exercise will increase load bearing qualities of the musco-skeletal system but if training and nutrition are not optimised, bucked shins, micro-fractures, haemorrhage and stress fractures may occur. Therefore, special attention needs to given to mineral and vitamin supply. There is a risk that young racehorses may receive diets deficient in calcium, relative to the increased need for accelerated bone metabolism at onset of training. In conjunction with this the requirements of vitamin D also increase in young horses entering training because of increased bone modelling. When feeding traditional straight grains a balancer or supplement are recommended. To maintain a healthy digestive tract and good welfare of young horses in training an adequate supply of structural fibre is required when stabled a level of at least 1.2% of BW as forage feed (DM) is recommended. In addition continued grazing during the growing and training period will help with temperament and prevention of behavioural problems but also with nutrient balance and digestive tract health.
Keywords: Ko; young horse; growth; exercise; nutrient requirements; health